Mencintai Alam dalam Upacara Loka Po’o Suku Lio Mego - Maro, Kornelius (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2017)
The article highlights one of the local wisdoms of the ethnic Lio Mego, namelyloka po’o. The tradition is a ritual for the fertility of the soil. Loka po’o offers a meaningful value when people have been discussing about ecology. In the ritualloka po’o, the Lio Mego are convinced that the nature is just a reflection of the Highest Reality. The nature has a soul, namely the anima which is supposed to be preserved and not to be exploited blindly. Human beings are participating in the nature. Besides ecological aspect, the loka po’o tradition also offers another values such as divine aspect (divinity), unity, as well as democracy. Such values are surely denoting the values of Pancasila, the five basic principles of the country, the Republic of Indonesia